Microsurgical Resection of Cerebral Arteriovenous Malformation: Our Precious Experience - Irsyad, Muhammad Ari; Hutagalung, Tommy Rizky; Putra, Prawira Buntara; Tala, Muhammad Ihsan Zulkarnain (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Introduction : Intracranial ateriovenous malformation (AVM) is a non-neoplastic congenital vascular abnormality which appears as a mass lesion composed of tangled blood vessels connecting arteries and veins in the brain. Case Report : Twenty seven years old male was present in our emergency department (ED) with decreased of conciousness and reccurent generalized seizure. The physical examination reveal the patient Glasgow coma scale (GCS) of 12 points (E4M5V3). Head CT scan with contrast shows contrast enhancing lesion on the frontoparietal region with extension to right lateral ventricle which suggest vascular lesion. We performed surgical resection of the AVM using the temporary clip on M2 branch which supply the nidus to reduce the risk of bleeding on operation. Discussion : Patients with grade I or II AVM tolerate resection with acceptable morbidity, whereas those with a grade IV or V AVM may be considered for conservative management because of the high anticipated risk of surgical morbidity Conclusion : AVMs are abnormalities of the intracranial vessels that constitute a connection between the arterial and venous systems and lack an intervening capillary bed. Microsurgical excision of the AVM involves a craniotomy, careful dural opening with circumferential nidus dissection until complete AVM resection is achieved.